Tingkat Antusiasme dan Pemahaman Belajar Siswa dalam Mengenal Kebudayaan Daerah Istimewa Yogyakarta di SDN 1 Karangantu terhadap Media Pembelajaran Mind Mapping - Ratna Dewi; Andrean Andrean; Ayu Nurlaela; Raffi Ridho Ramadhan (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
This research aims to measure the level of enthusiasm and understanding of third grade students at SDN 1 Karangantu in learning about the culture of Yogyakarta Special Region using mind mapping learning media. The background of this research is the need for innovative learning methods that can increase student engagement and understanding of the material, especially about culture. The research method used is descriptive qualitative with a literature approach and field review. Data was collected based on scientific literature and field observation review at SDN 1 Karangantu to measure students' enthusiasm and understanding of learning using mind mapping. The research subjects were all third grade students of SDN 1 Karangantu. The results showed that the use of mind mapping media has a positive impact on students' learning enthusiasm, which can be seen from their active participation and interest in learning activities. In addition, students' learning understanding of DIY culture also increased significantly. This indicates that mind mapping is effective as a learning medium that can help students organise information, understand concepts, and remember details of DIY culture better.